DKK3 promotes renal fibrosis by increasing MFF-mediated mitochondrial dysfunction in Wnt/β-catenin pathway-dependent manner - Jianling Song; Yanxia Chen; Yan Chen; Minzi Qiu; Wenliu Xiang; Ben Ke; Xiangdong Fang (Renal Failure)
Background Chronic kidney disease (CKD) lacks effective treatments and renal fibrosis (RF) is one of CKD’s outcomes. Dickkopf 3 (DKK3) has been identified as an agonist in CKD. However, the underlying mechanisms of DKK3 in CKD are not fully understood.Methods H2O2-treated HK-2 cells and ureteric obstruction (UUO) mice were used as RF models. Biomarkers, Masson staining, PAS staining, and TUNEL were used to assess kidney function and apoptosis. Oxidative stress and mitochondria function were also evaluated. CCK-8 and flow cytometry were utilized to assess cell viability and apoptosis. Western blotting, IHC, and qRT-PCR were performed to detect molecular expression levels. Immunofluorescence was applied to determine the subcellular localization. Dual luciferase assay, MeRIP, RIP, and ChIP were used to validate the m6A level and the molecule interaction.Results DKK3 was upregulated in UUO mouse kidney tissue and H2O2-treated HK-2 cells. Knockdown of DKK3 inhibited oxidative stress, maintained mitochondrial homeostasis, and alleviated kidney damage and RF in UUO mice. Furthermore, DKK3 silencing suppressed HK-2 cell apoptosis, oxidative stress, and mitochondria fission. Mechanistically, DKK3 upregulation was related to the high m6A level regulated by METTL3. DKK3 activated TCF4/β-catenin and enhanced MFF transcriptional expression by binding to its promoter. Overexpression of MFF reversed in the inhibitory effect of DKK3 knockdown on cell damage.Conclusion Upregulation of DKK3 caused by m6A modification activated the Wnt/β-catenin pathway to increase MFF transcriptional expression, leading to mitochondrial dysfunction and oxidative stress, thereby promoting RF progression.